1991
DOI: 10.1111/j.1440-1827.1991.tb01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine Adenocarcinoma of the Bilateral Axillae

Abstract: A case of apocrine adenocarcinoma arising in the bilateral axillae is reported. The patient was an 88 year old Japanese male who complained of a mass lesion and puslike discharge in the right axilla. Another mass was also noticed in the left axilla. No other neoplastic lesion was found in other sites of the body. The histologic appearances of the bilateral axillary tumors were almost identical. Both were adenocarcinoma with varying degrees of differentiation, composed of glands and nests of atypical epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Yoshida et al also reported aSMA results identical to those seen here. 5 ''This is the first reported case of apocrine carcinoma with detailed results of immunohistochemistry using epithelial membrane antigen''…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Yoshida et al also reported aSMA results identical to those seen here. 5 ''This is the first reported case of apocrine carcinoma with detailed results of immunohistochemistry using epithelial membrane antigen''…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, only Yoshida et al have reported a case of apocrine adenocarcinoma arising in bilateral axillae. 5 Their case occurred in an 88 year old Japanese man who complained of bilateral axillae masses, which consisted of different degrees of adenocarcinoma, foci of in situ carcinoma, and non-neoplastic but hyperplastic apocrine gland. Their histological findings were very similar to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five cases of axillary apocrine carcinoma with benign apocrine tumours are reported in the literature. [3][4][5][6][7] All these cases were of elderly Japanese men who had bilateral benign apocrine tumours. The Japanese authors suggested that apocrine hyperplasia is a precursor of cancer and that apocrine adenoma, hyperplasia and carcinoma may be successive steps in the linear progression to carcinoma.…”
mentioning
confidence: 99%
“…Using paraffin-embedded sections and various monoclonal antibodies, such as CEA, EMA, BRST-2 and BRST-3, the diagnosis of apocrine carcinoma can be readily evaluated immunohistochemically. [2][3][4] BRST-2, a useful marker of apocrine carcinoma of the breast, 5 is also positive for apocrine sweat gland carcinoma but not for eccrine carcinoma. 6 However, in another report this antibody was shown not to be useful to distinguish apocrine and eccrine carcinoma since both normal apocrine and eccrine glands were positive.…”
Section: Discussionmentioning
confidence: 99%